Model Menu Engineering Inklusif: Kajian Profitabilitas Terhadap Menu Ramah Vegetarian dan Vegan di Hotel Berbintang - Dewi, Ila Huda P.; Sutiadiningsih, Any; Salsabilla, Adinda Maulita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The growing shift toward plant-based dietary patterns in the hospitality industry demands innovative strategies in menu management, particularly in balancing profitability with consumer dietary preferences. This study aims to develop an inclusive menu engineering model to evaluate and enhance the performance of vegetarian and vegan menu items in starred hotel restaurants. A quantitative descriptive-analytical approach was employed, using sales data collected over the past year from four- and five-star hotels in major Indonesian cities. Menu performance was analyzed using the Kasavana & Smith menu engineering method, focusing on popularity and contribution margin, and further expanded into an inclusive model incorporating sustainability values and customer satisfaction. The findings indicate that while vegetarian and vegan dishes offer competitive contribution margins, their popularity remains relatively low compared to regular items. Hence, strategic interventions are needed, including product reformulation, consumer education, and marketing optimization. The proposed inclusive menu engineering model provides a practical framework for menu decision-making that aligns financial goals with evolving consumer expectations for healthier, ethical, and environmentally friendly food options. This research contributes to advancing sustainable practices within hotel restaurant operations in Indonesia